PEMANFAATAN PELEPAH DAUN KELAPA SAWIT FERMENTASI DENGAN PENAMBAHAN BERBAGAI LEVEL BIOMOL+ TERHADAP PENGGEMUKAN DOMBA JANTAN LOKAL - doni akbari (Jurnal Peternakan Integratif, 2015)
ABSTRACT The research aimed was to determine the level of Biomol+ on oil palm frond in feed base on waste of palm oil plantations on local male sheeps fattening. This research was conducted at the Laboratory of Animal Biology, Animal Science Studied Program, Faculty of Agriculture, University of Sumatera Utara  from November 2013 until February 2014. This research using completely randomized design(CRD) consists of 4 treatments (P0 = 0% Biomol+; P1 = 5% Biomol+; P2 = 10% Biomol+ and P3 = 15% Biomol+) and 3 replications with the average of body weight 6,82  ±  0,42 kg. The results showed that feed intake, average daily gain and  feed conversion ratio (FCR) was highly significant influenced by level Biomol+. Increasing level of Biomol+ increased feed intake, average daily gain and improved  feed conversion ratio (FCR). The research conclusion is the level Biomol+ 15%  show best result base on feed intake, average daily gain feed conversion for male local sheeps fattening. Keywords: Loca lmale sheeps, Biomol+, feed intake, average daily gain and feed conversion (FCR).